Efeito do exercício físico no controle à insônia e ansiedade dos acadêmicos de Educação Física na Universidade Pública do Norte do Tocantins no contexto da pandemia de Covid-19 - Neres, Marcela De Sousa (Universidade Federal do Tocantins, 2023)
The objective of the study was to investigate the effect of physical exercise on improving insomnia and symptoms of anxiety in Physical Education students at a public University